The Role of Technology in Detecting Cyber Risk and Improving Internal Audit: A Systematic Review - Nasruddin, Nadya Annisa; Pomtoh, Grace T; Kusumawati, Andi (Jurusan Akuntansi Fakultas Ekonomi Universitas Siliwangi, 2023)
This research aims to explore the literature that examines the role of technology in assisting cyber risk detection and improving company internal audit in the digital era. The method used in this research is systematic literature review (SLR). Data sample collected using Watase-Uake database and articles from other sources with Q1-Q4 index starting from 2014-2023. The selected articles have passed several specified criteria to produce a total number of 25 articles. The result shows that technology plays an important role in increasing the efficiency and effectiveness of cyber risk detection and internal audit processes. This research contributes to providing an overview regarding the benefits of technology in helping companies detect cyber risks and improve the quality of their internal audits